Baseline hydroponic study for biofortification of bread wheat genotypes with iron and zinc under salinity: growth, ionic, physiological and biochemical adjustments. (16th March 2023) - Naz, Tayyaba; Iqbal, Muhammad Mazhar; Akhtar, Javaid; Saqib, Muhammad
Abstract: Salinity is one of the major abiotic stresses that is deteriorating soil fertility and reducing essential nutrients acquisition by plants around the world. Among staple food, wheat can be a primary source of micronutrients like Fe and Zn. The saline/saline-sodic and calcareous soils are deficient in Fe and Zn. In these regards, the aim of present study was to screen out wheat genotypes which can efficiently utilize Fe and Zn in saline conditions. Therefore, ten wheat genotypes (i.e., Ujala-2016, Punjab-2011, Galaxy-2013, Faisalabad-2008, Anaj-2017, SARC-I, SARC-VIII, Lasani-2008, Sehar-2006 and Inqalab-91) were exposed to varying rates of Zn (0.2, 0.4 µM) and Fe (25, 50 µM) under saline and normal conditions in a solution culture experiment. Salinity was developed by using NaCl salt, while the sources of Zn and Fe were ZnSO4 .7H2 O and FeSO4 .7H2 O, respectively. The data of various wheat growth and ionic parameters including root/shoot dry weight, chlorophyll contents, Zn, Fe, K and Na concentration in root and shoot of wheat genotypes were recorded using standard procedures. The results showed that Fe and Zn application significantly ( p  ≤ 0.05) increased wheat plant growth under salt stress. Among tested genotypes, Faisalabad-2008 and Galaxy-2013 performed better under saline conditions with maximum biomass production, Zn, Fe and K absorption. Thus, these both genotypes were found to be good source for future wheat breeding programs or can be grown by farmers owing to efficient Fe and Zn utilization as a gateway toward the production of Fe and Zn biofortified wheat under saline conditions.